2021
DOI: 10.1111/acel.13424
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell RNA‐Seq reveals a highly coordinated transcriptional program in mouse germ cells during primordial follicle formation

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…1). It has been previously reported that the initial stage of primordial follicle formation in mouse ovaries is embryonic 17.5 dpc (27). In the present study, CaMKII was mainly expressed in the ovarian cortex of 17.5 dpc embryos, where only a small number of primordial follicles were revealed (Fig.…”
Section: Expression Of Camkii In the Embryonic And Neonatal Mouse Ova...supporting
confidence: 68%
See 1 more Smart Citation
“…1). It has been previously reported that the initial stage of primordial follicle formation in mouse ovaries is embryonic 17.5 dpc (27). In the present study, CaMKII was mainly expressed in the ovarian cortex of 17.5 dpc embryos, where only a small number of primordial follicles were revealed (Fig.…”
Section: Expression Of Camkii In the Embryonic And Neonatal Mouse Ova...supporting
confidence: 68%
“…Formation of primordial follicles not only determines whether there are oocytes available for fertilization, establishment and maintenance of the primordial follicle reserve pool also directly determines the reproductive life span of female animals (32,33). It has been reported that in the ovaries of mice at 17.5 days of embryonic stage, only part of the cysts rupture to form a small number of primordial follicles (27). By contrast, in the ovaries of mice after birth, a large number of cysts rupture and primordial follicles are formed continuously, before formalizing the primordial follicle pool during the first 4-5 days after birth (34).…”
Section: Discussionmentioning
confidence: 99%
“…We next sought to dissect the alternative RNA processing events that contributed to isoform changes between GV and MII oocytes. According to a benchmarking study ( Mehmood et al, 2020 ) and our experience ( He et al, 2021b ), we first adopted SUPPA2 ( Trincado et al, 2018 ) and rMATS ( Shen et al, 2014 ) for comparison of annotated alternative events. SUPPA2 investigated seven types of alternative events including skipped exons, retained introns, mutually exclusive exons, alternative 5′ or 3′ splice sites, and alternative first or last exons; however tandem UTRs were not included.…”
Section: Resultsmentioning
confidence: 99%
“…In an SKLRB (State Key Lab of Reproductive Medicine)independent project, many differentially expressed genes (DEGs) were screened to be the regulators of primordial follicle destiny (in chronological order, germ cells in cysts, germ cells undergoing cyst breakdown, and germ cells in follicles) in PND (post-natal-day) 0.5 ovaries through single-cell RNA sequencing, DEGs with a gradually decreasing expressing level from cyst towards follicles are thought to be more important for those in cysts or even for germ cells in meiotic prophase. 22 One of these DEGs was Fbxw24 (gene ID 382106), a gene encoding a protein with both F-box-like and WD-40 domains. The F-box domain mediates protein-protein interactions in a variety of contexts, including polyubiquitination, 23 whereas the WD-40 domain is proposed to coordinate interactions with other proteins and/or small ligands, playing a wide variety of functions in numerous eukaryotes.…”
Section: Oocyte-predominant Fbxw24 Is Essential For Female Fertilitymentioning
confidence: 99%